Sufism : A Beginner's Guide - Chittick, William C. (London ONEWORLD, 2000)
William C. Chittick, the leading scholar in the field, offers a compelling insight into the origins and key themes of Islamic mysticism.
Include Index
Keywords: Religion -- Sufism -- Sufism--Study and teaching